(Im)maturity in Tumor Ecosystem - Mortezaee, Keywan; Majidpoor, Jamal (Frontiers in Oncology, 2022)
Tumors have special features that distinct them from their normal counterparts. Immature cells in a tumor mass and their critical contributions to the tumorigenesis will open new windows toward cancer therapy. Incomplete cellular development brings versatile and unique functionality in the cellular tumor ecosystem, such what seen for highly potential embryonic cells. There is evidence that maturation of certain types of cells in this ecosystem can recover the sensitivity of tumor. Therefore, understanding more about mechanisms contributed to this immaturity will render new therapeutic approaches in cancer therapy. Targeting such mechanisms can be exploited as a supplementary to the current immunotherapeutic treatment schedules, such as immune checkpoint inhibitor (ICI) therapy. The key focus of this review to discuss about the impact of (im)maturity in cellular tumor ecosystem on cancer progression, focusing mainly on immaturity in immune cell compartment of tumor, as well as on stemness of tumor cells.